Proliferative activity in oral pyogenic granuloma: A comparative immunohistochemical study - Rezvani Gita; Azarpira Negar; Bita Geramizadeh; Zeynab Rahimi (Wolters Kluwer Medknow Publications, 2010)
Context: Pyogenic granuloma (PG) is one of the most common reactive vascular lesions in the oral mucosa, which has been divided into the lobular capillary hemangioma (LCH) and the non lobular type (non-LCH) as two distinct entities, on the basis of some investigations. Aims: This study aims to compare the proliferative and angiogenic activity of two histological types of PG to determine whether they have two distinct types of biological behavior. Settings and Design: In this retrospective cross-sectional study, immunostaining was performed on 10 cases of each type of PG. Materials and Methods: About 4μm sections were cut from formalin-fixed paraffin-embedded blocks and each specimen was stained with both anti-CD31 and anti-Ki-67 antibodies simultaneously. Labeling index (LI) was determined for both types by counting Ki-67 and CD31 positive cells separately and simultaneously in 1000 stromal and luminal cells. Micro vessel count (MVC), the mean number of micro vessels in five areas at Χ200 magnification, was also determined for both groups. Statistical Analysis: The results were statistically compared using the Mann-Whitney U-test. Results: Ki-67 LI in LCH (5.4 ± 2.4) was higher than non-LCH (3.9 ± 3.9). The percentage of CD31 positive cells in LCH (28.5 ± 22) was lower than non-LCH (37.1 ± 20.8) and simultaneously immunostaining for both markers in LCH type (2.4 ± 2.1) was higher than non-LCH (1.2 ± 1). The MVC was approximately 77.35 ± 34.6 and 82.6 ± 42.7 in the lobular areas of LCH and central areas of non-LCH PG, respectively. These differences were not statistically significant. Conclusions: These results demonstrate a higher proliferation activity in endothelial cells of LCH PG than in non-LCH.